2022
DOI: 10.14309/crj.0000000000000806
|View full text |Cite
|
Sign up to set email alerts
|

Acute Severe Ulcerative Colitis After mRNA Coronavirus Disease 2019 Vaccination: Can mRNA Vaccines Unmask Inflammatory Bowel Diseases?

Abstract: BNT162b2 is a messenger RNA vaccine for the prevention of the novel coronavirus disease 2019 caused by severe acute respiratory syndrome coronavirus 2 infection. The widespread use of this vaccination has brought along several adverse events. We present a patient with newly diagnosed ulcerative colitis after BNT162b2 vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Several case reports mentioned UC triggered by messenger RNA (mRNA) vaccines such as BNT162b2 and mRNA-1273, and Çağatay and colleagues believed that the BNT162b2 vaccine may have triggered a worsening of UC by activating nuclear factor-κB and interferon-alpha. [9][10][11] However, subsequent presentation of UC combined with arthropathy after receiving protein subunit vaccine as MVC-COVI1901 vaccine has not been previously reported. We speculate that the pathogenesis of this case could be correlated to the components of the MVC-COVI1901 vaccine (spike protein S-2P adjuvanted with CpG 1018 and aluminum hydroxide).…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports mentioned UC triggered by messenger RNA (mRNA) vaccines such as BNT162b2 and mRNA-1273, and Çağatay and colleagues believed that the BNT162b2 vaccine may have triggered a worsening of UC by activating nuclear factor-κB and interferon-alpha. [9][10][11] However, subsequent presentation of UC combined with arthropathy after receiving protein subunit vaccine as MVC-COVI1901 vaccine has not been previously reported. We speculate that the pathogenesis of this case could be correlated to the components of the MVC-COVI1901 vaccine (spike protein S-2P adjuvanted with CpG 1018 and aluminum hydroxide).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that COVID-19 infection is associated with the development of autoimmunity and can trigger multiple autoimmune diseases, ranging from organ-specific to systemic autoimmune and inflammatory diseases [ 8 ]. Multiple cases of de novo inflammatory bowel diseases following COVID-19 infection or vaccination have been reported [ 9 , 10 ]. As direct causation is difficult to prove, an association remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 vaccination status does not seem to have an influence on disease onset or evolution [89,90]. In the adult population, however, there are new cases of IBD with onset reported after a previous SARS-CoV-2 infection, most of them with severe evolution, reflecting another aspect of the intricate SARS-CoV-2-IBD relationship [97][98][99][100]. Oral prednisone, then infliximab due to worsening hematochezia.…”
Section: De Novo Pediatric Ibd Post Covid-19mentioning
confidence: 99%